2021
DOI: 10.29413/abs.2021-6.6-1.5
|View full text |Cite
|
Sign up to set email alerts
|

A clinical case of central retinal artery occlusion after pneumonia caused by SARS-CoV-2 (COVID-19)

Abstract: In domestic and foreign medical periodical literature, highlighting the problem of ophthalmopathology against the background of coronavirus infection, the lesion of the anterior segment of the eye is most often described. It is extremely hard to find reports about pathology of the retina, optic nerve or central parts of the visual analyzer. However, it is widely acknowledged that there is a high risk of developing coagulopathy against the background of COVID-19 infection, which leads to occlusion and thrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…[ 46 ] Several studies showed potential occlusion of the central retinal artery/vein and vein due to hypercoagulability. [ 47 48 49 50 51 52 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 ] Several studies showed potential occlusion of the central retinal artery/vein and vein due to hypercoagulability. [ 47 48 49 50 51 52 ]…”
Section: Discussionmentioning
confidence: 99%